Factors affecting capital adequacy ratio of Syrian Banks (Journal of Hama University, 2024)
The study aims to specify internal factors affecting capital adequacy ratio of Syrian private banks listed at Damascus Stock Exchange. The study used data from annual financial reports of banks during the period from 2010 to 2021. Five internal factors were investigated and capital adequacy ratio is computed by dividing total equity by total assets. A fixed effect regression model was chosen after comparing between different regression models for panel data. Results showed that credit risk, profitability and loan ratio have significant effect on capital adequacy whereas the effect of portfolio risk and bank size was not statistically significant.
Keywords: Syrian private banks, capital adequacy, internal factors, regression models for panel data